Analysis of the epidemiological situation and dynamics of the incidence of sexually transmitted infections in the Russian Federation over a ten-year period (2012-2022) - Margarita R. Rakhmatulina; Elena Yu. Novoselova; Lidia E. Melekhina (State Scientific Center of Dermatovenereology and Cosmetology, 2024)
Sexually transmitted infections (STIs) are socially significant diseases and require close attention due to the multifactorial causes that influence their spread. In 2012-2022, the Russian Federation maintained a downward trend in the incidence of STIs (from 267.6 to 91.3 cases per 100 thousand population), established since 1998 in all age groups. In 2022, compared to 2012, the incidence rates decreased: syphilis - by 42.7%; gonococcal infection - by 77.7%; trichomoniasis - by 75.8%; chlamydial infections - by 72.1%; anogenital herpetic infection - by 51.2%; anogenital (venereal) warts - by 36.5%. But at the same time, in 2021 and 2022, there was an increase in the incidence of syphilis and gonococcal infection: compared to 2019, the increase in the incidence of syphilis was 25.9%, and that of gonococcal infection - 5.2%. The increase in the incidence of syphilis was largely due to an increase in this indicator in the Central (from 18.1 to 37.3 cases per 100 thousand population) and Northwestern (from 14.5 to 16.2 cases per 100 thousand population) federal districts ( FO). An increase in the incidence of gonococcal infection in 2022 compared to 2019 was observed in the Central (+26.3%), Northwestern (+31.2%) and Ural (+27.6%) Federal Districts.